Escitalopram vs duloxetine in acute treatment of major depressive disorder: Meta-analysis and systematic review - Benchalak Maneeton (2018)
© 2018 Maneeton et al. Background: Previous evidence indicated that efficacy of escitalopram (Esc) and duloxetine (Dul) was comparable in the treatment of major depressive disorder (MDD). Since such studies had small sample sizes, this study purposefully applied a systematic review to determine the efficacy, acceptability, and tolerability those antidepressants in treatment of MDD. Participants and methods: The following primary databases were searched in July 2017: Scopus, PubMed, CINAHL, and Cochrane Controlled Trials Register. Any randomized controlled trials (RCTs) of Esc comparison with Dul in the treatment of MDD were included in this review. The primary efficacy of outcome was the pooled mean-changed scores of the rating scales for the standardized rating scales for depression. Results: A total of 1,120 randomized subjects from 3 RCTs were collected for synthesis in the present meta-analysis. The mean-changed scores of the Hamilton Depression Rating Scale (HAMD) and Clinical Global Impression – Severity, overall response rate by the HAMD, and remission rate by the HAMD and Montgomery–Asberg Depression Rating Scale (MADRS) in the Esc-and Dul-treated groups showed no significant differences. However, the mean-changed score of the MARDS, mean-end scores of Clinical Global Impression – Improvement, and overall response by the MADRS in the Esc-treated group were greater than that of the Dul-treated group. Although the overall discontinuation rate had no significant differences between the 2 groups, the discontinuation rate due to adverse events in the Esc-treated group was greater than that of the Dul-treated group. Limitations: This review had limited eligible studies. Conclusion: This review indicated the efficacy in the acute treatment of Esc vs Dul varied relying on measurements across the studies. However, the tolerability of Esc was superior to Dul in acute MDD treatment. Therefore, selection between the 2 antidepressants may depend on the tolerability of MDD patients. Due to limited included studies in this review, more large-scale and well-defined RCTs in such patients should be carried out to determine these outcomes.